SISTEM PEMBERDAYAAN MASYARAKAT NELAYAN DI KABUPATEN TAKALAR - Nasriah Akil (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
Development as a process of social change to the order of a society which is considered better is not a new phenomenon, because the process involves the construction of improvements. In other words, development is a process of changes and its planned growth into improvements oriented toward modernization, nation building and socio-economic progress.